2013
DOI: 10.1038/ijir.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of meal replacements with reduced-fat diet on weight, sexual and endothelial function, testosterone and quality of life in obese Asian men

Abstract: Sexual dysfunction is more prevalent in obese than in normal-weight men. Meal replacements (MRs) are useful weight-loss strategies. We randomized obese (body mass index 27.5 kg m(-2), waist circumference (WC) 90 cm) Asian men (mean age 40.5 years, range 30-61) to a conventional reduced-fat diet (CD) (n=24) or MR-based plan (n=24) to reduce daily intake by 400 kcal for 12 weeks. There were significantly greater reductions in weight (4.2 ± 0.8 kg), WC (4.6 ± 0.7 cm), calorie and fat intake in the MR group, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
23
1
Order By: Relevance
“…Our findings are in contrast to prior reports [6,7,35,36] where improvements in the SDI or IPSS occurred following weight losses of 2-6-12.3 kg over 8–52 weeks. We note that an improvement in the storage LUTS score occurred for those with the presence of features of lower urinary tract symptoms relating to storage symptoms at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to prior reports [6,7,35,36] where improvements in the SDI or IPSS occurred following weight losses of 2-6-12.3 kg over 8–52 weeks. We note that an improvement in the storage LUTS score occurred for those with the presence of features of lower urinary tract symptoms relating to storage symptoms at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…While some studies have shown that comprehensive lifestyle changes that included weight loss but not as the sole intervention improved LUTS symptoms, none studied weight loss alone and none included a group of men who specifically had symptomatic LUTS. [1820] While in general the studies showed that dietary interventions that induce weight loss may improve LUTS with greater weight loss correlating with greater improvements, these studies suffer from multiple limitations. First , none of the studies specifically targeted men with symptomatic LUTS.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Oksuz and Malhan30 reported that men without diet-based lifestyle changes are at higher risk for MSD, and Khoo et al 15 found that a reduced-fat diet in obese Chinese men enhances male sexual function. In this study, however, vegetables and milk and dairy products were risk factors for MSD.…”
Section: Discussionmentioning
confidence: 99%